PERILAKU BALOK KAYU MERANTI SEBAGAI BAHAN BANGUNAN UTAMA RUMAH TRADISIONAL ACEH - Helwiyah Zain (Center for Research and Community Service (LPPM) University of Abulyatama, 2015)
The objective of this research is to get the behaviour of Meranti wood beams as a material of Aceh traditional building. The behaviour is to gain the relationship between load-deflection of wood beams test. Meranti woods are got from 6 locations of woods machinery i.e: 3 locations in the area Banda Aceh and other 3 lcations in Aceh Besar. The flexural test was used 5x7x120 cm wood beams size, and total 30 specimens.from those 6 locations. To get other supporting data, the other test was done i.e.: physical characteristic and mechanical characteristic. Physical characteristic was done with specific gravity test, and moisture content test which are 10 specimens each test. Mechanical characteristic was done with tensile test and compression test which are 10 specimens each test. The result of the test obtained moisture content was 13,19% at 28,9o C temperature. Average specific gravity was 0,429. Tensile strength parallel to main fiber was 448,1 kg/cm2 at 0,53 % average maximum strain. Compression strength parallel to main fiber was 316,9 kg/cm2 at 0,41 % average maximum strain. Average modulus of elasticity from tensile test was found 84.547 kg/cm2. Flexural characteristic was a relationship between load-deflection plotted as a graph in the text. Based on these result could be concluded that Meranti woods was appropriated to be material building Aceh traditional houses.